Product Marketing Strategy For Micro, Small and Medium Enterprises : Strategi Pemasaran Produk UMKM : Usaha Mikro Kecil Menengah - Khoirun Nisak; Diah Krisnaningsih (Academia Open, 2024)
This research was conducted to find out about how the comparison or advantages between conventional and sharia marketing strategies in MSME players. This research uses the Systematic Literature Review method. This research procedure has 4 stages consisting of identification, screening, eligibility, and inclusion. The literature in this study comes from several journals from Google Scholar. After searching for articles with a range of 2011 to 2023, there were 20 articles that discussed the Marketing Strategy of MSME Products. The purpose of the marketing strategy is to facilitate MSME players in Indonesia. Highlights : Conventional vs. Sharia Marketing: Understand the comparative advantages. Systematic Literature Review: Methodology for comprehensive analysis. Impact on MSMEs: Enhancing accessibility and effectiveness of marketing strategies. Keywords : Conventional marketing, Sharia marketing, MSME players, Systematic Literature Review, Product